2020
DOI: 10.17358/jma.17.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Technology Adoption and Technical Efficiency of Oil Palm Smallholder Plantation in Riau and West Kalimantan

Abstract: This study was conducted to assess the role of adoption of oil palm cultivation technology that has been recommended by the government (RI Regulation of the Minister of Agriculture No 131 / Permentan / OT.140 / 12/2013 concerning Guidelines for Good Oil Palm Cultivation) on production efficiency from smallholder plantations on the dependent smallholder and independent smallholder in Riau and West Kalimantan. Specifically, this study is: (1) to analyze the factors that influence the level of production and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The competitive advantage of a business depends on the achievability of the supply chain management practices. The performance of SMEs's success is linked with the accessibility of communication and information technology (Ariyanto et al, 2020;Fitriani et al, 2019;Juliannisa & Siswantini, 2021;Singh et al, 2010)…”
Section: Discussionmentioning
confidence: 99%
“…The competitive advantage of a business depends on the achievability of the supply chain management practices. The performance of SMEs's success is linked with the accessibility of communication and information technology (Ariyanto et al, 2020;Fitriani et al, 2019;Juliannisa & Siswantini, 2021;Singh et al, 2010)…”
Section: Discussionmentioning
confidence: 99%
“…(Ginting et al, 2020) showed that education had a positive and significant effect on economic growth. (Ariyanto et al, 2020;Pham et al, 2021) state that to promote the implementation of sustainable agricultural practices, we advise enhancing collaboration across peers, farmer groups, and extension agents.…”
Section: B Education Levelmentioning
confidence: 99%
“…Pupuk Iskandar Muda has the lowest efficiency level. In practice, firms can enhance their technical efficiency by improving their technology and managerial (Arianto et al, 2020). The scale efficiency measurement finds opposite results.…”
Section: The Fertilizer Industry Efficiencymentioning
confidence: 99%